DNA methylation at an enhancer of the three prime repair exonuclease 2 gene (TREX2) is linked to gene expression and survival in laryngeal cancer - Weigel, Christoph; Assenov, Yassen; Winkler, Volker; Santi, Irene; Kaucher, Simone; Lorenzo Bermejo, Justo; Lasitschka, Felix; Herold-Mende, Christel; Dyckhoff, Gerhard; Boukamp, Petra; Plass, Christoph; Becher, Heiko; et al. (Clinical epigenetics, 2019)
Genetic aberrations in DNA repair genes are linked to cancer, but less is reported about epigenetic regulation of DNA repair and functional consequences. We investigated the intragenic methylation loss at the three prime repair exonuclease 2 (TREX2) locus in laryngeal (n = 256) and colorectal cancer cases (n = 95) and in pan-cancer data from The Cancer Genome Atlas (TCGA).
Gesehen am 10.03.2020